CD8+ T-cell lymphocytes infiltration predict clinical outcomes in Wilms’ tumor - Keykhosro Mardanpour; Mahtab Rahbar; Sourena Mardanpour; Nyousha Mardanpour; Mansour Rezaei (Tumor Biology)
The abundance and location of CD8+ tumor-infiltrating lymphocytes demonstrate important facets of the anticancer immune response. CD8-expressing lymphocytes have been used in immunotherapy for multiple cancers. This study aims to determine the association between the abundance and localization of CD8+ tumor-infiltrating lymphocytes and clinical outcomes of Wilms’ tumor. This retrospective study employed 42 pediatric patients diagnosed with Wilms’ tumor. CD8+ tumor-infiltrating lymphocyte counts were calculated based on the mean percentage of stroma occupied by CD8+ lymphocytes at the center and the invasive border of the tumor using immunohistochemistry. CD8+ tumor-infiltrating lymphocyte counts were significantly higher in the center and the invasive border of the early-stage tumor samples. CD8+ tumor-infiltrating lymphocytes in the invasive border and tumor center positively correlated with tumor invasion, regional lymph node invasion, histological type, metastasis, and stage of the tumor. A high CD8+ tumor-infiltrating lymphocyte scores at the invasive margin of the tumor correlated with low tumor recurrence. Low CD8+ tumor-infiltrating lymphocyte scores in the two tumor regions correlated with poor prognosis and shorter disease-free survival. Overall, these findings show that patients with high CD8+ tumor-infiltrating lymphocytes are associated with better clinical outcomes. Therefore, measuring the abundance of CD8+ tumor-infiltrating lymphocytes may be useful in predicting response to cancer immunotherapies.